Energy saving for an air conditioning system applied in a thin-film-transistor liquid-crystal display (TFT LCD) high-tech fabrication plant (Fab). (November 2022) - Lin, Tee; Zargar, Omid Ali; Wang, Zhi-Qing; Hu, Shih-Cheng; Shih, Yang-Cheng; Leggett, Graham
Abstract: Data collected from this research is used to calculate energy consumption of the thin-film-transistor liquid-crystal display (TFT LCD) air-conditioning system. These results are then used to determine how much energy can be saved and proposes to reduce the energy consumption of the chiller component of the air conditioning system. Analysis based on factory operation data collected in the past indicates that process machine operation accounts for 45% of total energy usage. In addition to the power consumption of the factory system, compressed dry air CDA accounted for 22% of the total energy consumption. The high temperature chiller accounted for 7% and ranks second, while third is FFU power consumption, accounting for 6%. When evaluating the feasibility of energy conservation, it is necessary to collect operating parameters and evaluate the operating efficiency of the equipment to identify potential changes to effect energy conservation. According to preliminary analysis of distribution and operation data, it is found that the current filter used in the fan filter frame (FFU) responsible for the clean room circulation is a traditional high-efficiency filter made of glass fiber. Glass fiber filters can be replaced with PTFE filters, offering potential energy savings associated with lower pressure drop. The factory does not add CDA cooling water waste heat recovery and utilization in the warm water system. After the addition of this recovery system, the cooling water temperature will increase by 0.6 °C and the estimated electric boiler energy saving is 1.86%.If the new generation high-efficiency chiller were installed, under typical operating conditions where the load is between 70% and 90%, annual efficiency is expected to be between 0.423 kW/RT and 0.412 kW/RT, which is expected to save 2.6% when compared with older generation chiller technology.; If two sets of the original chillers are replaced with one chiller in constant use and one in standby configuration, the annual efficiency is 0.4 kW/RT, saving 5.4%. Replacing a configuration of four sets with three in constant use and one in standby configuration, the annual efficiency is 0.388 kW/RT, saving 8.3%.